2003
DOI: 10.1111/j.1572-0241.2003.07664.x
|View full text |Cite
|
Sign up to set email alerts
|

Does bacterial gastroenteritis predispose people to functional gastrointestinal disorders? A prospective, community-based, case-control study

Abstract: Symptoms consistent with IBS and functional diarrhea occur more frequently in people after bacterial gastroenteritis compared with controls, even after careful exclusion of people with pre-existing FGIDs. The frequency is similar at 3 and 6 months. Our findings support the existence of postinfectious IBS and give an accurate estimate of its frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 15 publications
7
83
1
2
Order By: Relevance
“…Animal models and some preliminary human data suggest that this leads to excessive serotonin release from the mucosa. A prospective community-based, case-control study supports the existence of PI-IBS in some individuals (27). Symptoms consistent with IBS and functional diarrhea occur more frequently in people after bacterial gastroenteritis compared with controls, even after careful exclusion of people with pre-existing functional gastrointestinal disorders (FGIDs).…”
Section: Causesmentioning
confidence: 88%
“…Animal models and some preliminary human data suggest that this leads to excessive serotonin release from the mucosa. A prospective community-based, case-control study supports the existence of PI-IBS in some individuals (27). Symptoms consistent with IBS and functional diarrhea occur more frequently in people after bacterial gastroenteritis compared with controls, even after careful exclusion of people with pre-existing functional gastrointestinal disorders (FGIDs).…”
Section: Causesmentioning
confidence: 88%
“…Controls in these studies were either volunteers, patients from the same general practice or siblings or spouses of the patient. The PI-IBS incidence rate in these five studies ranged from 4 % [26] up to 17 % [27]. The calculated AR is also shown in Table 1.…”
Section: Dalysmentioning
confidence: 99%
“…Second, in this study we did not consider patient characteristics (such as gender, smoking or psychosocial comorbidity) as risk factors for developing PI-IBS. Similarly, we did not take into account the details of the gastroenteritis episode, such as duration or aetiology of the infection [10,22,27,35,36]. With regard to duration of gastroenteritis, previous studies revealed that the longer period patients have symptoms due to gastroenteritis or the larger effect these symptoms have, the higher the risk of having PI-IBS [36,37].…”
Section: Reported Casesmentioning
confidence: 99%
“…There is increasing evidence that acute infectious gastroenteritis (GE) can increase the risk of IBS, with several studies demonstrating that a significant number of GE patients develop PI-IBS [1,2,[18][19][20][21][22][23]. Campylobacter, Shigella, Salmonella and Escherichia coli infections as well as viral agents, including norovirus, and parasites have been associated with PI-IBS [5,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%